Assessment of hamas regime's foreign policy in protecting Palestinian national interest - Alsarhi, Abeer A.S (2016)
Foreign policy is essentially about the protection and achievement of the national interest of a state. But has that been the case with Palestine? Palestine, as a developing state currently under Israeli occupation, needs a strong foreign policy to protect its national interest. This study aimed to evaluate the Palestine's foreign policies under Hamas regime during the 2006-2013 periods. This study carries four objectives namely,first, to explore the vision of Hamas regime on the Palestine’s national interest. Second, to examine the principles adopted by Hamas regime in formulating its foreign policies. Third, to determine the factors that influence these foreign policies. Fourth, to assess Hamas’ success in protecting the national interests.Data were collected from face-to-face interview with five key persons in Hamas (the Prime Minister, two ministers from Foreign Affairs, a head of foreign relations, and one scholar in Palestinian studies). The data were then transcribed, coded and analyzed with inductive and comparative methods.The study shows that Hamas views the liberation of land through resistance can protect the national interests.The results reveal six principles namely Islamic ethics and controls; a strategic vision of liberation; supporting the resistance; protecting the national interests; noninterference in internal affairs; and independence of decision. These principles are considered as guidelines to protect the national interests.Moreover, the results show that there are internal factors (political system,security,peace agreements,the leadership of Fatah) and external factors (international siege, Israeli occupation,international quartet conditions, and lack of support from other nations) that influence Hamas regime’ relations. The study also shows that, despite the challenges Hamas faces, it has indeed succeeded in protecting them from threats both the national and international levels.Taken together, the study concludes that the foreign policies of Hamas Regime has greatly impacted on the protection of the national interests as reflected from its political visions,principles and practices in international relations.